Інтродукційний потенціал листяних кущів для створення кам’янистих садів у Поліссі та Лісостепу України - Kazanska, N.A.; Кuznetsov, S.I.; Vovk, R.Ja. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The article presents data on introduction potential shape variety of leafy shrubs and their forms for creating mountain park landscapes.